Ground stabilization in expansive soils using engineered plastic columns: A quantitative experimental study - Ng, Jun Shen; Muzamir, Hasan; Nedunchelian, N. Thevagar; Hoque, Md. Ikramul (Springer, 2026)
The escalating demand for sustainable approaches in rectifying ground conditions has led to the examination of novel materials. It investigates the potential of acrylonitrile butadiene styrene (ABS) formed into a granular column to reinforce the strength of clay soil, emphasizing its mechanical resilience and environmental reuse potential compared to other materials. Experimental procedures involved Preparing unreinforced and reinforced samples (50 mm diameter, 100 mm height). ABS columns were drilled at 8, 12, and 16 mm diameters with heights of 60, 80, and 100 mm. Drilling Bits of specific diameters were used to create boreholes, and the backside was applied to compact the ABS plastic in three layers. Unconfined compression (UCT) and unconsolidated undrained (UU) tests were implemented, with three replicated trials per design. The influencing factors on soil strength such as the number of columns, column diameter, column height, area substitute proportion, column intrusion proportion, column intrusion to column diameter proportion, volume intrusion proportion, and confining pressure were examined to evaluate the performance of distinct ABS column designs. The results demonstrated significant improvements in shear strength and overall stability when ABS columns were employed to resist lateral loads. Based on regression analysis, a forecasting model was developed as an estimating equation for reinforced Kaolin soil. This model provides a pragmatic framework for identifying granular column applications in soft clay soils under actual site conditions. The research highlights both the operational and environmental advantages of ABS in ground rectification, aligning with the sustainable development goals